Accelerated ageing of micron- and nano-sized aluminum powders: Metal content, composition and non-isothermal oxidation reactivity. (May 2019) - Paravan, Christian; Verga, Alberto; Maggi, Filippo; Galfetti, Luciano
Abstract: Nano-sized Al (nAl) is an attractive candidate for the performance enhancement of current solid propellant formulations, and its characteristics are relevant for the development of innovative solid fuels for hybrid rocket propulsion. Nano-sized Al powders feature a higher reactivity than their micron-sized counterpart. While desirable for effective energy conversion during the combustion, this characteristic yields possible powder storage issues. This paper investigates the ageing behavior of air-passivated nAl powders under two different relative humidity conditions (RH) of 80% and 10%. Fresh and aged powders are characterized by active metal content determination (CAl ), electron microscopy, X-ray diffraction, and thermal analysis. The marked sensitivity of nAl (40 nm) to ageing is testified by a nearly full CAl loss in just 24 h (with RH = 80%). Under the same condition, the conventional 30 μm-counterpart loses only 13% of the original active metal content in a time of 336 h. Highlights: In a dry environment, no degradation of nano-sized Al was noted over 14 days. Nano-/micron-sized Al different behavior after pristine alumina shell corruption. In humid environment, micron-sized Al metal content reduction ends in 7 days. In humid environment, nano-sized Al metal content is consumed in less than 30 h. Morphology and texture of particles are altered by the aging process.